Plutonium-238: The Fuel Crisis - Ricardo Bastos Smith; Fernanda Cristina Romero; Roberto Vicente (Brazilian Journal of Radiation Sciences)
Plutonium-238 is currently still the best fuel to power satellites to be sent to deep space in regions where the solar panels can no longer efficiently receive the sunlight. For 50 years, the National Aeronautics and Space Administration (NASA) has used this radioisotope as a fuel in radioisotope thermoelectric generators (RTGs) installed on satellites such as Pioneer 10 and 11, Voyager 1 and 2, Cassini-Huygens and New Horizons, as well as the various rovers sent to the Moon and to Mars, among others. Plutonium-238 is not a naturally occurring isotope on the planet, it was produced in greater quantity during the Cold War period as a by-product of the production of Plutonium-239 used for nuclear bombs. However, after the shutting down of the Savannah River reactors in 1988 and the ending of the Soviet Union in 1991, the United States stock of Plutonium-238 has been increasingly reduced, which threatens NASA's future space projects. This paper presents a brief bibliographic review about the subject, as well as commentaries on the options available to the United States, from restarting the production of this fuel, to possible alternatives for a new type of fuel or equipment that may supply the spacecrafts.